Comparison Between Surgical and Conservative Treatment for AOSpine Type A3 and A4 Thoracolumbar Fractures without Neurological Deficit: Prospective Observational Cohort Study - Emiliano Neves Vialle; Asdrubal Falavigna; André de Oliveira Arruda; Joana Bretas Cabral Rondon Guasque; Bárbara Miroski de Oliveira Pinto; Guilherme Finger; Ericson Sfreddo; André Martins de Lima Cecchini (Revista Brasileira de Ortopedia, 2023)
Abstract Objective To compare the clinical results between conservative (CS) and surgical treatment (CXS) of A3 and A4 fractures without neurological deficit. Methods Prospective observational study of patients with thoracolumbar fractures type A3 and A4. These patients were separated between the surgical and conservative groups, and evaluated sequentially through the numeric rating scale (NRS), Roland-Morris disability questionnaire (RMDQ), EuroQol-5D (EQ-5D) quality of life questionnaire, and Denis work scale (DWS) up to 2.5 years of follow-up. Results Both groups showed significant improvement, with no statistical difference in pain questionnaires (NRS: CXS 2.4 ± 2.6; CS 3.5 ± 2.6; p> 0.05), functionality (RMDQ: CS 7 ± 6.4; CXS 5.5 ± 5.2; p> 0.05), quality of life (EQ-5D), and return to work (DWS). Conclusion Both treatments are viable options with equivalent clinical results. There is a tendency toward better results in the surgical treatment of A4 fractures.